Implementation of the Medan City Outer Ring Area Development Acceleration Program (Study in Medan Marelan District) - Ismail AB; Ahmad Albar Tanjung; Sukardi Sukardi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The acceleration of development in the outer ring area of ​​Medan is carried out by the Medan City Government in order to distribute development throughout the Medan area, one of which is the Medan Marelan District. In its Development Plan, the City of Medan carries out an Accelerated Development Program which does not only focus on development in the urban center area but also accelerates development in the outer ring area/outer part of Medan. This is done for the even distribution of Medan City Development, both in the Social, Economic, Political, and Cultural fields. This research method is a descriptive research method with a qualitative approach. The location of this research is Medan Marelan District, Medan. The informants in this study consisted of key informants, namely the Head of Medan Marelan District. The main informants, namely staff/apparatus in the Medan Marelan sub-district office, and additional informants, namely community leaders. Data collection techniques used in this study were interviews, observations, literature studies, and documentation studies. The result of the research is that the condition or existence of existing infrastructure development in Medan Marelan District, Medan City is implemented quite effectively and is able to add and improve several facilities and infrastructure, not only road infrastructure, health infrastructure, educational infrastructure, but also add economic infrastructure. Although the infrastructure development carried out in the Medan Marelan Subdistrict area has not been optimal, the actions taken by the Medan Marelan Subdistrict Government have brought about better changes and made the atmosphere and community environment safer and more comfortable. And factors that support infrastructure development in Medan Marelan District include the support of all residents for government policies and a safe and harmonious environment in the community.